Conceitos fundamentais da Teologia de Karl Rahner lidos à luz da parábola do filho pródigo (Lc 15, 11-32) - Castelo Branco, Judikael (Kairós: Revista Acadêmica da Prainha, 2021)
The text addresses some concepts from Karl Rahner’s theology following the reading of the biblical passage from Lk 15,11-32. The goal is not to bring together texts of different natures, but to use the narrative of one as a map to the reading of another. Thus, the object studied is Rahner’s theology, while the Lucan text serves as a framework for the placement of the concepts considered. However, the exercise offers us not only a key to the interpretation of Rahner’s work, but leads us to reflections that directly encounter some of the most disturbing questions of Christian spirituality today, namely, how to understand religious indifference, on the one hand, and the return of fundamentalism, on the other. In Rahnerian figures, the problem can only be posed seriously considering the notion of God’s self-communication and the implications that this term has for the understanding of the human being.